2018
DOI: 10.1128/mbio.00820-18
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Responses in a War of Small Molecules between a Plant-Pathogenic Bacterium and Fungi

Abstract: Small-molecule signaling is one major mode of communication within the polymicrobial consortium of soil and rhizosphere. While microbial secondary metabolite (SM) production and responses of individual species have been studied extensively, little is known about potentially conserved roles of SM signals in multilayered symbiotic or antagonistic relationships. Here, we characterize the SM-mediated interaction between the plant-pathogenic bacterium Ralstonia solanacearum and the two plant-pathogenic fungi Fusari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…The SMs are synthesised by accessory biosynthetic pathways thought to be important for a range of processes, including spore development, spore survival and fungal communication. Recent advances promote the view that fungal mycotoxins are fitness factors that help to establish a niche for protection from competing microbes [101,102].…”
Section: The Janus Face Of Filamentous Fungimentioning
confidence: 99%
“…The SMs are synthesised by accessory biosynthetic pathways thought to be important for a range of processes, including spore development, spore survival and fungal communication. Recent advances promote the view that fungal mycotoxins are fitness factors that help to establish a niche for protection from competing microbes [101,102].…”
Section: The Janus Face Of Filamentous Fungimentioning
confidence: 99%
“…The genomes of filamentous fungi are rich in gene clusters coding for biosynthetic pathways of SMs with various bioactivities, yet only few of them are expressed under laboratory conditions (Brakhage and Schroeckh, ; Chiang et al , ). The production of some SMs is induced in co‐cultures of fungi with bacteria (Cueto et al , ; Oh et al , ; Schroeckh et al , ; Ola et al , ; Spraker et al , ) and it has been hypothesized that these SMs function, depending on their concentration, either as signaling molecules or as growth inhibitors in the chemical defense of these fungi against bacterial competitors and antagonists (Brakhage et al , ; Andersson and Hughes, ; Netzker et al , ). Besides biotic stress, abiotic stress can also trigger expression of silent SM gene clusters (Scherlach and Hertweck, ; Gressler et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides biotic stress, abiotic stress can also trigger expression of silent SM gene clusters (Scherlach and Hertweck, ; Gressler et al , ). However, there are only few cases where the regulation of SM gene clusters involved in bacterial‐fungal interactions (BFIs) was studied at a molecular level (Schroeckh et al , ; Nützmann et al , ; Spraker et al , ). The SM gene clusters of filamentous fungi include non‐ribosomal peptide synthetases (NRPSs), polyketide synthases (PKSs) and terpene synthases (TSs) (Lackner et al , ; Bills et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…And the melanin biosynthesis is an ideal target for development of targeted speci c inhibitor to control the fungal pathogens [39]. Schumacher [40] and Spraker et al [41] reported that the production of pigments in lamentous fungi was not directly involved in their growth and development, but that it might contribute to survival in unfavorable environmental stress conditions such as UV radiation, heat, and oxidation, bacterial invasion and pathogenesis related mechanisms. Based on this result, we hypothesize that melanin pigment might be the reason for the caffeine tolerance of the fungus.…”
Section: Discussionmentioning
confidence: 99%